EVALUASI PEMBELAJARAN IPA BERBASIS PRAKTIKUM DI UPT SPF SDN MONGISIDI 2 KOTA MAKASSAR - Nggalene, Stevania; Icayanti; Johan, Elsa Meliani; Manapa', Juinda Arruan; Bungin, Rita; Burhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of practicum-based science learning evaluation at UPT SPF SDN Mongisidi 2, the assessment instruments used by teachers, as well as the challenges and effectiveness of its implementation. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and literature review. The collected data were analyzed using descriptive qualitative analysis to provide an in-depth description of the learning evaluation process. The results showed that the practicum-based science learning evaluation was implemented systematically, starting from the planning, implementation, and reflection stages. In the evaluation process, teachers used various assessment instruments to evaluate students' participation, group collaboration, skills in using tools and materials, observation abilities, conceptual understanding, and practicum outcomes. Several challenges were identified, including limited practicum tools and materials, time constraints, and the lack of experience among some students in conducting practicum activities. Nevertheless, practicum-based science learning was found to be effective in improving students' understanding of the subject matter because it provides direct, active, and meaningful learning experiences. Therefore, practicum-based science learning evaluation can effectively support the achievement of learning objectives.